Measuring Disconnection from Nature: Validation of the Nature Disconnectedness Scale and Its Psychological and Environmental Correlates - Hasselberg,Benjamin (2025)
In order to solve planetary health, the human-nature relationship has to be understood in more detail. Therefore, the current study aimed to validate and assess construct, convergent, divergent, and predictive validity of the Nature Disconnectedness Scale. Using data from 312 participants in Sweden, confirmatory factor analyses found support for a structure consisting of three dimensions and eight subdimensions, aligning with a priori theoretical expectations. The scale showed strong internal consistency and strong negative correlations with nature relatedness, confirming its close relationship to the construct. Meaningful associations with Big Five traits, anxiety, depression, life satisfaction, and harmony in life were found. Nature disconnection was found to predict lower levels of self-reported pro-environmental behaviors after controlling for demographic variables. These findings offer a complementary framework to existing connectedness research and suggest that the Nature Disconnectedness Scale is a valuable tool for operationalizing the human-nature relationship, particularly for identifying and addressing disconnection in populations with weak or disrupted ties to the natural world. Future research should confirm the structure of the scale in a different and larger sample.
Keywords: human-nature relationship; nature connection; nature disconnection; environmental psychology; pro-environmental behavior